A Review of Educational Data Mining Tools & Techniques - Hamza, Haitham Alagib Alsuddig; Kommers, Piet (International Journal of Educational Technology and Learning, 2018)
The purpose of this paper is to present a review study on the use of the tools and techniques of Education Data Mining (EDM); through the use of data mining techniques such as classification, aggregation, the correlation rules and the disclosure of cases and apply on the student grades to show the benefits of applying the techniques of data mining in the academic field to obtain a clear understanding of the factors success and failure of students. The paper presented a definition of the concept of (EDM) and then presents of several previous studies that used many different techniques of data mining. The paper concluded to review the most important applications of (EDM) and classification according to the objectives and methods used and General framework procedural can be use in (EDM).